2014
DOI: 10.1021/nl5006004
|View full text |Cite
|
Sign up to set email alerts
|

GaAs/AlGaAs Nanowire Photodetector

Abstract: We demonstrate an efficient core-shell GaAs/AlGaAs nanowire photodetector operating at room temperature. The design of this nanoscale detector is based on a type-I heterostructure combined with a metal-semiconductor-metal (MSM) radial architecture, in which built-in electric fields at the semiconductor heterointerface and at the metal/semiconductor Schottky contact promote photogenerated charge separation, enhancing photosensitivity. The spectral photoconductive response shows that the nanowire supports resona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
207
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(213 citation statements)
references
References 37 publications
2
207
1
Order By: Relevance
“…The significant attention is due to the vast scope of technical applications [2][3][4][5][6] as well as the capability to conduct fundamental studies, such as the search for Majorana bound states [7,8]. Another broad field of interest concerns the utilization for spintronic devices, which exploit the spin degree of freedom of the charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The significant attention is due to the vast scope of technical applications [2][3][4][5][6] as well as the capability to conduct fundamental studies, such as the search for Majorana bound states [7,8]. Another broad field of interest concerns the utilization for spintronic devices, which exploit the spin degree of freedom of the charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Many materials and structures including quantum dots [90][91][92], nanotubes [93][94][95][96], and nanowires [97][98][99] have been studied and considered to be good alternatives for silicon-based photodetectors. Interestingly, most of the 2D semiconductors are sensitive to light, heat, and ambient which makes them very attractive for applications in optoelectronic device sensing from infrared to the ultraviolet regime.…”
Section: Photodectorsmentioning
confidence: 99%
“…Krogstrup et al reported that a solar cell made from NWs can even break the Shockley-Queisser limit [62]. In addition, III-V NWs have been widely studied for use in detectors, single-photon sources and transistors [63][64][65].…”
Section: Low-dimensional Nanostructures Of Gasb Materialsmentioning
confidence: 99%